The Influence of Self-Efficacy and English Language Skills on Career Motivation and Its Impact on Students' Career Aspirations at the Faculty of Economics and Business, Al-Amien Prenduan Islamic University - Nurul Hidayati; Luthfatul Qibtiyah; Uswatun Hasanah; Rosyidi Rosyidi (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study was to build an understanding of the role of self-efficacy and English language skills on career motivation and its impact on students' career aspirations at the Faculty of Economics and Business, Al-Amien Prenduan Islamic University. This research is categorized as Explanatory Research, aiming to explain causal relationships among variables. Data were collected using a structured questionnaire, and the sampling technique used was purposive sampling. The study involved 90 students, and the data were analyzed using the Structural Equation Model (SEM) with AMOS software to ensure comprehensive and accurate testing of the proposed model. The results of this study indicate that self-efficacy has a positive and significant effect on career motivation, while English language skills also show a positive and significant influence on career motivation. Furthermore, career motivation has a positive and significant impact on students' career aspirations. These findings emphasize that strong confidence and adequate English proficiency can encourage students to develop clearer and higher career goals, highlighting the importance of improving both competencies in higher education settings.